Fabrication and characterization of Si quantum dots and SiO2 tunnel barriers grown by a controlled oxidation process - Sutikno, Madnasri; Uda, Hashim; Zul Azhar, Zahid Jamal (IOP Publishing Ltd, 2009)
Link to publisher's homepage at http://iopscience.iop.org